2016
DOI: 10.1088/0964-1726/25/7/075013
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among grain size, annealing twins and shape memory effect in Fe–Mn–Si based shape memory alloys

Abstract: In order to clarify the relationship among grain size, annealing twins and the shape memory effect in Fe-Mn-Si based shape memory alloys, the Fe-21.63Mn-5.60Si-9.32Cr-5.38Ni (weight %) alloy with a grain size ranging from 48.9 μm-253.6 μm was obtained by adjusting the heating temperature or heating time after 20% cold-rolling. The densities of grain boundaries and annealing twins increase with a decrease in grain size, whereas the volume fraction and width of stress-induced ε martensite after 9% deformation at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 33 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…In another study conducted by Murakami et al [120], ranging grain size between 20-200 μm was reported to have no clear effect on SME values [121]. Based on the outcome of the different researches mentioned above, an investigation was conducted [122] where Fe- respectively. It was found that for Fe-21.63Mn-5.60Si-9.32Cr-5.38Ni alloy, the grain size reduction causes the SME to decline.…”
Section: B) Fe and Fe-based Smasmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study conducted by Murakami et al [120], ranging grain size between 20-200 μm was reported to have no clear effect on SME values [121]. Based on the outcome of the different researches mentioned above, an investigation was conducted [122] where Fe- respectively. It was found that for Fe-21.63Mn-5.60Si-9.32Cr-5.38Ni alloy, the grain size reduction causes the SME to decline.…”
Section: B) Fe and Fe-based Smasmentioning
confidence: 99%
“…In face-centred cubic (fcc) metals, deformation twinning is observed, especially when the stacking fault energy (SFE) is low to medium, after thermo-mechanical treatment involving annealing and cold working [122][123][124][125]. For high SFE elements, such as Ni and Al, twinning is rarely observed [35].…”
Section: C) Cu-and Cu-based Smasmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourthly, the formation of annealing twins should be suppressed in Fe-Mn-Si based SMAs [34,[68][69].…”
Section: Criteria Of Achieving Giant Recovery Strains In Polycrystallmentioning
confidence: 99%
“…The relationship between annealing twins and grain size in austenitic stainless steels continues to interest researchers due to the presence of various alloy contents in these steels. Wang et al (2016) clarified that the densities of grain boundaries and annealing twins increased with a small increase in grain sizes, which resulted in decreased shape of the memory effect in Fe-Mn-Si-based shape-memory alloys. Jin et al (2015) found that the number of annealing twin boundaries of Inconel 718 did not increase with an increase in the average grain size.…”
Section: Introductionmentioning
confidence: 99%